PENERAPAN MODEL PEMBELAJARAN STUDENT CENTERED LEARNING (SCL) DALAM PEMBELAJARAN MENULIS PANTUN SISWA KELAS VII SMPN 1 BANTAN KABUPATEN BENGKALIS - Depika Pina Sufa; Nursal Hakim; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of the Student Centered Learning (SCL) learning model on the writing skills of seventh grade students of SMPN 1 Bantan, Begkalis district.  The method used is a quantitative research method with the Student Centered Learning (SCL) learning model.  The design of this research is One Group Pretest-Postest Design.  The sampling technique uses total sampling.  The sample in this study amounted to 27 people in one class Data collection technique is a test technique.  The test is used to assess students' rhyming writing skills Data analysis techniques using the Shapiro-Wilk normality test, then test the hypothesis using the Wilcoxon Test.  The results show that there is an effect of the application of the Student Centered Learning (SCL) learning model to the poetry writing skills of Grade VII students of SMPN 1 Bantan, Bengkalis Regency.   Key Words: Student Centered Learning (SCL) Learning Model, Writing Skills, Pantun